Home Birth in Rural Zambia: The Role of Intimate Partner Violence and Autonomous Decision‐Making. (12th March 2021) - Beck, Dana; Veliz, Philip T.; Munro‐Kramer, Michelle; Ngoma, Thandiwe; Scott, Nancy; Kaiser, Jeanette L.; Musonda, Gertrude; Lori, Jody R.
Abstract : Introduction: Skilled care is indicated as a measure to prevent the deaths of pregnant women across sub‐Saharan Africa. Despite this, many women continue to give birth at home. There has been little attention as to how the experience of intimate partner violence (IPV) or autonomous decision‐making about place of birth influences home births in rural Zambia. This study explores how markers of sociocultural gender inequities (prevalence of IPV and autonomous decision‐making) correlate with home birth in rural Zambia. Methods: This secondary analysis uses quantitative data from a baseline household survey with women who had given birth within the past 13 months in rural Zambia. Control variables shown to be significant in the literature were included in the model, and binary logistic regression was used to assess the influence of IPV and autonomous decision‐making on home birth. Results: This sample included 2381 women from rural Zambia, of whom 384 reported a home birth within the past 13 months. Women who were autonomously making the decision about where to give birth were more likely to have a home birth (adjusted odds ratio [AOR], 1.729; SE, 0.210; 95% CI, 1.362‐2.194; P < .001). Self‐report of experiencing physical IPV in the past 2 weeks was not significant in predicting home birth (AOR, 0.783; SE, 0.181; 95% CI, 0.496‐1.234; P = .293). Women who self‐identified as Tumbuka or other, were able to afford school fees, had completed secondary education or higher, were married, and had 4 or more antenatal care visits were significantly less likely to report a home birth. Discussion: This quantitative analysis did not corroborate findings from other research that implicates IPV as a predictor of home birth. Additionally, autonomous decision‐making was not associated with a decrease in home births. Future work should incorporate qualitative or mixed methods strategies to comprehensively explore household‐ and facility‐level interventions to promote facility birth.